Layered dry-method silicon-based negative electrode plate, preparation method thereof and battery
By designing and fabricating a layered dry silicon-based anode sheet, the problems of high energy consumption in the wet process of lithium-ion batteries and poor performance of dry anode sheets have been solved, achieving low impedance and good cycle performance of high-energy-density batteries, which are suitable for large-scale applications.
Patent Information
- Application Number
- CN202510982395.8
- Authority / Receiving Office
- CN · China
- Patent Type
- Applications(China)
- Current Assignee / Owner
- Filing Date
- 2025-07-16
- Publication Date
- 2025-10-31
AI Technical Summary
Existing wet process technology for lithium-ion batteries suffers from high energy consumption, low production efficiency, high environmental risks, poor processability, and poor electrical performance. Furthermore, dry process anode sheets, especially high-energy-density silicon-based anode sheets, lack reasonable component control and electrode structure design, resulting in poor electrode adhesion, wettability, and cell performance.
The design employs a layered dry-process silicon-based negative electrode sheet, comprising a first dry-process electrode film close to the current collector and a second dry-process electrode film far from the current collector. The first film contains active materials, binder system A, and conductive agents, while the second film contains oxide solid electrolyte. The electrode sheet is prepared by binder fiberization and hot-pressing composite methods, optimizing the component ratio and layered structure.
It improves the processability and electrical performance of the electrode, reduces battery impedance, improves rate and cycle performance, and reduces environmental pollution and manufacturing costs caused by solvent use, showing promise for large-scale application.
Smart Images

Figure CN120878736A_ABST
Abstract
Description
Technical Field
[0001] This invention relates to the field of lithium-ion batteries, and more particularly to a layered dry-process silicon-based negative electrode sheet, its preparation method, and the battery thereof. Background Technology
[0002] Currently, the mainstream electrode coating method for lithium-ion batteries is the wet process, which involves dispersing active materials, binders, and conductive agents in an organic solvent such as NMP or deionized water, stirring evenly, coating the mixture onto a current collector, and then drying it. However, with the rapid development of lithium battery technology, the drawbacks of wet electrodes are becoming increasingly apparent, mainly in the following aspects: 1) Economically, the solvents used in wet electrodes require large-scale drying and recycling equipment, resulting in high energy consumption and the need for sufficient factory space; 2) In terms of production efficiency, the components are added step-by-step during the homogenization process, and uniform dispersion must be ensured, leading to longer production times. 1) Long process time and low efficiency; 2) Environmentally, wet slurry processing, especially the positive electrode solvent, is generally NMP, which has a certain degree of toxicity. The production and recycling process poses a threat to human health and the environment; 3) In terms of processability, there is a risk of cracking and peeling when wet electrodes are used to make thick electrodes; 4) In terms of performance, the binder is prone to floating during the drying process of wet electrodes, resulting in uneven distribution and low peeling force. During the slurry process, the binder will form a coating on the surface of the active material, which will hinder the electrical contact between active particles and the conductive agent, resulting in poor conductivity. In addition, the residual solvent has a negative impact on the electrical performance.
[0003] To overcome the aforementioned problems, dry electrode technology has become a key research direction in the industry. Compared with traditional wet processes, dry electrodes mix and mold various electrode components into a self-supporting electrode film without the use of solvents. Dry molding technology mainly includes powder compression, powder spraying, and binder fiberization. Since Tesla acquired Maxwell, its supercapacitor dry electrode preparation process based on binder fiberization has become a research focus. Patent CN 112687833B provides a method for preparing dry electrode sheets, in which raw material powders are mixed, heated, and fiberized to obtain electrode powder, which is then subjected to vertical and horizontal rolling to obtain a film. The film and foil are then bonded and rolled to form the electrode sheet. Patent CN119920818A simultaneously adds a first binder and a second binder to the dry electrode, improving the adhesion of the dry electrode and enhancing the battery's initial efficiency, rate capability, cycle life, and other electrical performance. The 118588862A dry-process battery membrane adopts a composite structure. The porous membrane serves as an intermediate support layer between the first and second dry-process electrode membranes, which improves the strength of the electrode sheet, avoids breakage during the production process, improves the production efficiency of dry-process electrode sheets, and enhances battery life and rate performance.
[0004] In existing technologies, there are relatively few developments for dry-process negative electrode sheets, especially high-energy-density silicon-based negative electrodes. The lack of reasonable component control and electrode structure design results in poor key indicators such as electrode adhesion, wettability, and conductive network, as well as poor high energy density and long-cycle power performance of the battery cell. Summary of the Invention
[0005] Objective of the Invention: In a first aspect, this application provides a layered dry-process silicon-based negative electrode sheet, which includes a current collector and an active material layer on the surface of the current collector. The active material layer includes a first dry-process electrode film close to the current collector and a second dry-process electrode film away from the current collector. The first dry-process electrode film includes an active material, a binder system A, and a conductive agent. The second dry-process electrode film includes an oxide solid electrolyte. The addition of the oxide solid electrolyte greatly improves the ion and electron transport rates, thereby improving the cell rate and cycle performance, and comprehensively improving the overall processability and electrical performance of the electrode sheet.
[0006] Secondly, this application provides a method for preparing a layered dry silicon-based negative electrode sheet. By controlling the composition and ratio, a layered silicon-based negative electrode sheet is prepared by binder fiberization and hot pressing composite method. Combining the characteristics and advantages of different layers of electrode sheets, the electrode sheet ends exhibit good processability and peeling force.
[0007] Thirdly, this application provides a battery, a lithium-ion battery using the layered dry-process silicon-based negative electrode sheet of this application. Through DCR and EIS testing, the battery exhibits lower impedance and good rate capability. This invention has a novel design, simple implementation method, and excellent performance, and has prospects for large-scale application.
[0008] Technical solution:
[0009] Regarding the first aspect, a layered dry-process silicon-based negative electrode includes a current collector and an active material layer attached to the surface of the current collector, wherein the active material layer includes a first dry-process electrode film close to the current collector and a second dry-process electrode film away from the current collector.
[0010] The first dry electrode film includes an active material, a binder system A, and a conductive agent, wherein the binder system A is a combination of PTFE and PAA;
[0011] The second dry electrode membrane includes an active material, a binder PTFE, an oxide solid electrolyte, and a conductive agent, wherein the oxide solid electrolyte is one of LATP, LLZO, and LLTO.
[0012] Furthermore, the content of each component in the first dry electrode film is as follows: active material 92~97wt%, binder system 3~8wt%, and conductive agent 0.3~1.5wt%.
[0013] Furthermore, the content of each component in the second dry electrode film is as follows: active material 92~97wt%, binder PTFE 2.5~5wt%, oxide solid electrolyte 0.5~3wt%, and conductive agent 0.3~1.5wt%.
[0014] In the adhesive system A, PTFE is a fibrous component, and PAA has both good peel strength and cohesive strength, which allows it to bond well with the foil and has a good inhibitory effect on the expansion of silicon-based negative electrodes.
[0015] The preferred amount of oxide solid electrolyte added in this application is 0.5~3wt%. Too much addition will lead to a decrease in the energy density of the cell, while too little addition will not effectively improve the rate capability.
[0016] Furthermore, in the first dry electrode and the second dry electrode film, the active material is a mixture of silicon-based negative electrode and artificial graphite, wherein the silicon-based negative electrode is one of silicon-oxygen, high-efficiency silicon-oxygen, and nano-silicon-carbon, and the proportion of the silicon-based negative electrode in the active material is 5-50%.
[0017] The conductive agent includes single-arm carbon nanotubes, and the amount of single-arm carbon nanotubes added in both the first dry electrode and the second dry electrode film is 0.3~1wt%.
[0018] Optionally, the conductive agent is a mixture of dot-shaped or linear conductive agents and single-arm carbon nanotubes.
[0019] Furthermore, the thickness of the first dry electrode film is 50~150μm, and the thickness of the second dry electrode film is 20~150μm.
[0020] Furthermore, the current collector is a copper foil or a carbon-coated copper foil, and the foil thickness is 6-8 μm.
[0021] Regarding the second aspect, a method for preparing a layered dry-process silicon-based negative electrode sheet includes the following steps:
[0022] Preparation of the first dry electrode membrane: The components of the first dry electrode membrane are mixed evenly according to the proportion, subjected to high-speed shearing and fiberization, and the fiberized material is hot-pressed into a film to obtain the first dry electrode membrane.
[0023] Preparation of the second dry electrode membrane: The components of the second dry electrode membrane are mixed evenly according to the proportion, subjected to high-speed shearing and fiberization, and the fiberized material is hot-pressed into a film to obtain the second dry electrode membrane.
[0024] Preparation of layered dry-process silicon-based negative electrode sheet: The current collector, the first dry-process electrode film and the second dry-process electrode film are stacked in sequence and then hot-pressed to obtain the layered dry-process silicon-based negative electrode sheet.
[0025] Furthermore, in the preparation of the first dry electrode film and the preparation of the second dry electrode film, the mixing speed is 500~1000 rpm and the mixing time is 30~120 min; the hot pressing temperature is 80~120℃.
[0026] Furthermore, in the preparation of the layered dry silicon-based negative electrode sheet, the hot-pressing composite temperature is 80~160℃.
[0027] Regarding the third aspect, a battery includes a positive electrode, a separator, an electrolyte, and a layered dry-process silicon-based negative electrode sheet as described in claims 1 to 8.
[0028] Beneficial effects:
[0029] 1) A layered dry-process silicon-based anode electrode includes a current collector and an active material layer on the surface of the current collector. The active material layer includes a first dry-process electrode film close to the current collector and a second dry-process electrode film away from the current collector. The first dry-process electrode film includes an active material, a binder system A, and a conductive agent. The second dry-process electrode film includes an oxide solid electrolyte. By controlling the composition and ratio of the first and second dry-process electrode films and combining the characteristics and advantages of different electrode layers, the electrode end exhibits good processability and peel strength. When paired with a nickel-cobalt-manganese ternary cathode, the battery exhibits lower impedance and good rate capability as verified by DCR and EIS tests. This invention has a novel design, simple implementation, and excellent performance, and has prospects for large-scale application. The high-energy-density silicon-based dry-process anode electrode avoids the use of solvents, reduces environmental pollution and manufacturing costs, improves production efficiency, and improves the overall performance of materials.
[0030] 2) A layered dry-process silicon-based negative electrode sheet was designed and synthesized, which exhibits lower impedance at the battery end, which is beneficial to the rate and long-cycle performance.
[0031] 3) The PAA+PTFE bonding system is used near the current collector electrode layer to balance flexibility, peel strength and mechanical properties; oxide solid electrolyte is added away from the current collector electrode layer to further improve electrode expansion, improve electrolyte wettability and comprehensively improve the battery's electrical performance. Attached Figure Description
[0032] Figure 1 This is a schematic diagram of the layered dry-process silicon-based negative electrode sheet (copper foil double-sided hot-pressed composite) structure of the present invention;
[0033] Figure 2 EIS performance diagrams of single-sided dry-process silicon-based negative electrode sheets prepared in Example 1 and Comparative Example 1 of this invention.
[0034] Figure label:
[0035] 1. Current collector; 2. First dry electrode film; 3. Second dry electrode film. Detailed Implementation
[0036] To make the technical solution of the present invention clearer, the present invention will be further described in detail below with reference to the accompanying drawings and specific embodiments.
[0037] Example 1: A method for preparing a layered dry-process silicon-based negative electrode sheet, comprising the following preparation steps:
[0038] 1) Positive electrode sheet production:
[0039] Weigh the positive electrode active material (nickel-cobalt-manganese ternary material): conductive agent: binder = 97:1:2 and place the component materials in a mixer to mix evenly. Place the evenly mixed material in a high-speed mixer for high-speed shearing and fiberization. The high-speed shearing speed is 1500~6000 rpm and the shearing time is 10~60 min. The fiberized material is then hot-pressed into a film. The hot-pressing process is carried out in a roller press at a roller pressing temperature of 80℃ and a pressure of 5~50t to obtain a dry positive electrode film. The obtained positive electrode film is then composited with aluminum foil at a temperature of 100℃ and a pressure of 30t to obtain a dry positive electrode.
[0040] 2) Negative electrode sheet fabrication:
[0041] The first dry electrode film was prepared by weighing the component materials according to the ratio of silicon carbon: artificial graphite: PTFE: PAA: conductive agent = 10:85:3:1:1 and placing them in a mixer. The mixture was stirred at 600 rpm for 1 hour to achieve uniform mixing. The mixed material was then placed in a high-speed mixer for high-speed shearing and fiberization at 1500 rpm for 30 minutes. The fiberized material was then hot-pressed into a film at a temperature of 100℃ and a pressure of 2t to obtain the first dry electrode film with a thickness of 100 μm.
[0042] The second dry electrode film was prepared by weighing the component materials according to the ratio of silicon carbon: artificial graphite: PTFE: LATP: conductive agent = 9:85:4:1:1 and mixing them evenly in a mixer (600 rpm, stirring for 1 h). The mixed material was then placed in a high-speed mixer for high-speed shearing and fiberization. The fiberized material was then hot-pressed into a film (100℃, pressure 2t) to obtain a second dry electrode film with a thickness of 100 μm.
[0043] In the first and second dry electrode films, the conductive agent components include single-arm CNTs and conductive carbon black, which account for 0.05% and 0.95% of the electrode film materials, respectively.
[0044] A layered dry-process silicon-based negative electrode sheet is obtained by sequentially stacking a copper foil (6μm thick), a first dry-process electrode film, and a second dry-process electrode film, and then hot-pressing them together. There are two types of hot-pressed negative electrode sheets: one is hot-pressed onto one side of the copper foil, used for coin cell evaluation; the other is hot-pressed onto both sides of the copper foil, with the structure shown below. Figure 1 Used for full-cell testing.
[0045] A lithium-ion battery according to this embodiment includes a positive electrode, a negative electrode, a separator, and an electrolyte. The battery is manufactured through processes such as stacking, tab welding, aluminum-plastic film encapsulation, and electrolyte injection.
[0046] Example 2, a method for preparing a layered dry-process silicon-based negative electrode sheet:
[0047] 1) The positive electrode sheet is made in the same way as in Example 1.
[0048] 2) Negative electrode sheet fabrication:
[0049] Preparation of the first dry electrode film: Weigh the component materials according to the ratio of pre-lithium silicon oxide: artificial graphite: PTFE: PAA: conductive agent = 10:85:3:1:1 and mix them evenly in a mixer. Place the mixed material in a high-speed mixer for high-speed shearing and fiberization. Then, hot press the fiberized material into a film to obtain the first dry electrode film.
[0050] Preparation of the second dry electrode film: Weigh the component materials according to the ratio of pre-lithium silicon oxide: artificial graphite: PTFE: LLZO: conductive agent = 9:84:4:2:1 and mix them evenly in a mixer. Place the mixed material in a high-speed mixer for high-speed shearing and fiberization. Then, hot press the fiberized material into a film to obtain the second dry electrode film.
[0051] In the first and second dry electrode films, the conductive agent components include single-arm CNTs and conductive carbon black, which account for 0.05% and 0.95% of the electrode film materials, respectively.
[0052] Copper foil, a first dry electrode film, and a second dry electrode film are stacked sequentially and then hot-pressed together to obtain a layered dry silicon-based negative electrode sheet.
[0053] A layered dry-process silicon-based negative electrode sheet is obtained by stacking copper foil (6 μm thick), a first dry electrode film (100 μm thick), and a second dry electrode film (100 μm thick) in sequence and hot-pressing composite. There are two types of hot-pressed negative electrode sheets: one is hot-pressed composite on one side of copper foil for coin cell evaluation, and the other is hot-pressed composite on both sides of copper foil for full cell testing.
[0054] A lithium-ion battery according to this embodiment includes a positive electrode, a negative electrode, a separator, and an electrolyte. The battery is manufactured through processes such as stacking, tab welding, aluminum-plastic film encapsulation, and electrolyte injection.
[0055] Comparative Example 1 differs from Example 1 in that:
[0056] Negative electrode fabrication: The negative electrode is a single-layer dry electrode, which is obtained by hot pressing a first dry electrode film with a thickness of 200 μm obtained according to the preparation method of Example 1 with a copper foil to obtain the negative electrode.
[0057] Comparative Example 2 differs from Example 1 in that:
[0058] Fabrication of negative electrode sheet: The negative electrode sheet is a single-layer dry electrode, which is obtained by hot pressing a second dry electrode film with a thickness of 200 μm obtained according to the preparation method of Example 1 with copper foil to obtain the negative electrode sheet.
[0059] Comparative Example 3 differs from Example 1 in that:
[0060] Negative electrode sheet fabrication: Copper foil, second dry electrode film, and first dry electrode film are stacked sequentially and then hot-pressed to obtain a layered dry silicon-based negative electrode sheet.
[0061] Performance testing:
[0062] 1) The negative electrode sheets prepared in Examples 1-2 and Comparative Examples 1-3 were subjected to peel strength tests.
[0063] 2) After the sodium-ion batteries prepared in Examples 1-2 and Comparative Examples 1-3 were formed and tested, the cell charge was adjusted to 50% SOC and the DCR performance was tested. The pulse current was 2.5C and the pulse time was 10s during the DCR test. The test results are shown in Table 1.
[0064] 3) The electrode sheet of Example 1 with a dry electrode laminated on one side of the copper foil and the electrode sheet of Comparative Example 1 were used to make a coin cell, and the EIS was tested. The test results are as follows: Figure 2 As shown.
[0065] Table 1: Test data of negative electrode sheets and cells in Examples 1-2 and Comparative Examples 1-3
[0066] Polaroid Peel strength (mN / mm) 50% SOC DCR (mΩ) Example 1 15.53 17.83 Example 2 15.61 18.83 Comparative Example 1 15.32 23.22 Comparative Example 2 10.67 19.65 Comparative Example 3 11.21 20.41
[0067] As can be seen from Table 1, the PTFE+PAA system exhibits better adhesion and is suitable as the first dry electrode film close to the current collector. The presence of oxide solid electrolyte can effectively reduce the overall impedance of the electrode, and the layered dry negative electrode design is reasonable, resulting in better overall performance.
[0068] from Figure 2It can be seen that the ohmic impedance and charge transfer impedance of Example 1 are both less than those of Comparative Example 1, indicating that the layered dry silicon-based negative electrode sheet can improve the ion transport rate, reduce the internal impedance of the electrode, and obtain better electrochemical performance.
[0069] The above description is merely a specific embodiment of the present invention and is not intended to limit the present invention. Those skilled in the art can make various modifications, alterations, substitutions and variations without departing from the design concept of the present invention, and all such modifications and alterations should fall within the protection scope of the present invention.
[0070] The embodiments described above are merely illustrative of several implementations of the present invention, and while the descriptions are specific and detailed, they should not be construed as limiting the scope of the present invention. It should be noted that those skilled in the art can make various modifications and improvements without departing from the concept of the present invention, and these modifications and improvements all fall within the scope of protection of the present invention. Therefore, the scope of protection of this patent should be determined by the appended claims.
Claims
1. A layered dry-process silicon-based negative electrode, characterized in that, It includes a current collector and an active material layer attached to the surface of the current collector, the active material layer comprising a first dry electrode film close to the current collector and a second dry electrode film away from the current collector; The first dry electrode film includes an active material, a binder system A, and a conductive agent, wherein the binder system A is a combination of PTFE and PAA; The second dry electrode membrane includes an active material, a binder PTFE, an oxide solid electrolyte, and a conductive agent, wherein the oxide solid electrolyte is one of LATP, LLZO, and LLTO.
2. The layered dry-process silicon-based negative electrode sheet according to claim 1, characterized in that, The content of each component in the first dry electrode film is as follows: active material 92~97wt%, binder system 3~8wt%, and conductive agent 0.3~1.5wt%.
3. The layered dry-process silicon-based negative electrode sheet according to claim 1 or 2, characterized in that, The content of each component in the second dry electrode membrane is as follows: active material 92~97wt%, binder PTFE 2.5~5wt%, oxide solid electrolyte 0.5~3wt%, and conductive agent 0.3~1.5wt%.
4. The layered dry-process silicon-based negative electrode sheet according to claim 3, characterized in that, In the first dry electrode and the second dry electrode film, the active material is a mixture of silicon-based anode and artificial graphite, wherein the silicon-based anode is one of silicon-oxygen, high-efficiency silicon-oxygen, and nano-silicon-carbon, and the proportion of the silicon-based anode in the active material is 5-50%. The conductive agent includes single-arm carbon nanotubes, and the amount of single-arm carbon nanotubes added in both the first dry electrode and the second dry electrode film is 0.3~1wt%.
5. A layered dry-process silicon-based negative electrode sheet according to any one of claims 1-2 and 4, characterized in that, The thickness of the first dry electrode film is 50~150μm, and the thickness of the second dry electrode film is 20~150μm.
6. A layered dry-process silicon-based negative electrode sheet according to claim 5, characterized in that, The current collector is a copper foil or a carbon-coated copper foil, and the foil thickness is 6-8 μm.
7. A method for preparing a layered dry-process silicon-based negative electrode sheet according to any one of claims 1-6, characterized in that, The preparation method includes the following steps: Preparation of the first dry electrode membrane: The components of the first dry electrode membrane are mixed evenly according to the proportion, subjected to high-speed shearing and fiberization, and the fiberized material is hot-pressed into a film to obtain the first dry electrode membrane. Preparation of the second dry electrode membrane: The components of the second dry electrode membrane are mixed evenly according to the proportion, subjected to high-speed shearing and fiberization, and the fiberized material is hot-pressed into a film to obtain the second dry electrode membrane. Preparation of layered dry-process silicon-based negative electrode sheet: The current collector, the first dry-process electrode film and the second dry-process electrode film are stacked in sequence and then hot-pressed to obtain the layered dry-process silicon-based negative electrode sheet.
8. The method for preparing a layered dry-process silicon-based negative electrode sheet according to claim 7, characterized in that, In the preparation of the first dry electrode film and the preparation of the second dry electrode film, the mixing speed is 500~1000 rpm and the mixing time is 30~120 min; the hot pressing temperature is 80~120℃.
9. A method for preparing a layered dry-process silicon-based negative electrode sheet according to claim 7 or 8, characterized in that, In the preparation of the layered dry silicon-based negative electrode sheet, the hot-pressing composite temperature is 80~160℃.
10. A battery, characterized in that, It includes a positive electrode, a separator, an electrolyte, and a layered dry-process silicon-based negative electrode sheet as described in claims 1 to 8.
Citation Information
Patent Citations
A dry electrode preparation method, the electrode prepared by the method, and its applications.
CN112687833B
Dry-method electrode, preparation method thereof and battery
CN119920818A